STUDI KELAYAKAN PENGEMBANGAN BANDAR UDARA ABDULRACHMAN SALEH MALANG - Sigit, Dwi Rahardjo (Program Doktor Ilmu Ekonomi, 2010)
City of malang is the second bigest city in east java province geografically be in malang regency area and direct adjoining batu tourism area.The existence of abdulrachman saleh airport as air t5ransportation infrastructure give malang economic development share.Since re-operated on june 2005, air traffic through abdulrachman saleh airport always rise significantly, especially after lapindo disaster in porong area that cause traffic jam on malang – surabaya highway everyday. Abdulrachman saleh airforce base tni-au use also to serve civil aviation, must be developed to meet international civil aviation organization (icao) requirment standard. That is why its need to built and developed efford.This visibility study discuss about development plan of abdulrachman saleh airport malang. With excute several finance sceme and its construction phase in order to meet projection of demand capacity until year 2035. Hope this airport development plan economically and financially feasible to buildKeyword : Airport development plan economically and financially feasible to build